Health Impact Associated with Pesticides Use among Vegetables Farmers in Nepal: A Secondary Analysis - Bhattrai, Saroj; Dhakal, Neelam; Poudyal, Anil; Dhimal, Meghnath (Journal of Nepal Health Research Council, 2021)
ackground: The trend of pesticide use in market-oriented vegetables is steadily increasing in Nepal. Farmers in developing countries use hazardous pesticides taking few or no safety measures. This study is aimed to assess health effects of pesticide exposure among vegetable farmers in Nepal.Methods: Analysis of secondary data obtained from Nepal Health Research Council was performed. A cross-sectional study on “Health Effects of pesticide among vegetables farmers and adaptation level of integrated pest management program in Nepal 2013” was conducted by Nepal Health Research Council among 660 farmers in four selected districts of Nepal in 2013/2014. The secondary data obtained were statistically analyzed by student’s‘t’ test, one-way analysis of variance and Pearson correlation statistics.  For all tests used, 5% level of significance was considered.Results: Fungicide and insecticides were commonly used pesticides by vegetable farmers in Nepal. Around 51% of the pesticides used were moderately hazardous (II) while, 28% were highly hazardous (Ib). Nearly 12% participants did not use any type of Personal Protective Equipments while spraying pesticides in the field. The prevalence of self-reported poisoning and low Acetylcholinesterase levels among farmers was 51% and 10.3% respectively. Acetylcholinesterase level was found to differ significantly in male as compared to female (P < .05). Conclusions: Almost half of the research participants had self-reported poisoning. Low prevalence of depressed Acetylcholinesterase levels was associated with high use of fungicide compared to organophosphate.Keywords: Acetylcholinesterase; organophosphate; pesticide